Pengaruh Pendekatan Balanced Scorecard Terhadap Kinerja Lembaga Amil Zakat Infaq Shadaqah Muhammadiyah (Lazismu) Kota Medan - Ainun Nahya Dwi Arizona; Yenni Samri Juliani Nasution; Laylan Syafina (Penerbit Jurnal Indonesia, 2022)
The Balanced Scorecard is a contemporary management tool used to boost an organization's ability to multiply financial performance. The use of the balanced scorecard in management promises a significant increase in the organization's ability to create wealth. The objectives of the BSC can be achieved through the cooperation of organizational institutions that always carry out an assessment of the institution itself, both in the field of services and in the facilities provided. Ensuring to maintain harmony between employees in carrying out their work, because it is one of the important factors for the survival of an institution. The advantage of the BSC is that it can provide a measure that can be used as a basis for strategic improvement. The purpose of this study is to discuss whether the perspective in the Balanced Scorecard has an effect on the performance of the Amil Zakat Infaq Shadaqah Muhammadiyah Medan City. This research was conducted using statistical methods. The results of this study were processed using the SPSS 26.0 program. This study showed that based on (t test) it was stated that the financial perspective had a positive effect on LAZISMU performance with a significance of 0.031 < 0.05. The customer perspective has a positive effect on the performance of LAZISMU with a significance of 0.003 <0.05. The internal business process perspective has a positive effect on the performance of LAZISMU with a significance of 0.026 < 0.05. The perspective of growth and learning has a positive effect on the performance of LAZISMU with a significance of 0.000 <0.05.